A Novel Method for Assessing Prosthesis Use and Accommodation Practices of People with Transtibial Amputation. Issue 4 (October 2018) - Sanders, Joan E.; Redd, Christian B.; Larsen, Brian G.; Vamos, Andrew C.; Brzostowski, Jacob T.; Hafner, Brian J.; Allyn, Katheryn J.; Henrikson, Katrina M.; McLean, Jake B.; Hinrichs, Paul
ABSTRACT: Introduction: Practitioners typically rely on patient self-report for information about prosthesis use and limb volume accommodation. Electronic monitoring may provide a more accurate and easier means of collecting these data. Methods: A novel low-profile sensor was used for 2 weeks to track when the limb was within the socket. Each participant also recorded daily prosthesis don times, doff times, and sock changes in a written log. Results: Participants (n = 21) wore their prosthesis frequently, for approximately 14.1 hrs/day (interquartile range [IQR], 12.5–14.9), and doffed their prosthesis for 0.5 hr/day (IQR, 0.1–1.2). Of those participants who performed sock changes, participants most often performed sock changes 0.4 times per day (IQR, 0.3–1.0) and socket releases (temporary doffs) 1.3 times per day (IQR, 0.5–3.8). Measured and self-reported beginning-of-prosthesis day were not significantly different ( P = 0.002), whereas end-of-prosthesis day were significantly different ( P = 0.573). Conclusions: The developed electronic monitor may improve recording of prosthesis use and monitoring of socket releases. Data collected in this study may serve as a starting point for characterizing socket wear and accommodation in people with limb loss.